Rage for order : essays in criticism - Warren, Austin, (Ann Arbor paperbacks, 1959)
Edward Taylor.--George Herbert.--Alexander Pope.--Gerard Manley Hopkins.--William Butler Yeats.--Nathanial Hawthorne.--Franz Kafka.--E.M. Forster.--Henry James.